ANALYSIS OF CORRELATION BETWEEN BEHAVIORS OF BROILER BREEDERS AND ENVIRONMENT VARIABLES - PENHA, NÁRIMA L. J.; OLIVEIRA, SANDRA C.; PEREIRA, DANILO F. (Revista Brasileira de Engenharia de Biossistemas, 2007)
To understand the poultry behavior it has earned importance in the modern poultry exploration;therefore express the complex social and environment interactions of the birds. This occurs becauseof the complex way of how environment affects the performance of the birds and, therefore, theanalysis of the behavior can provide greater efficiency and precision in the control of the environment.Moreover, also motivating these studies, the impact generated for the guarantees of welfare in thehouse of the animals that the European consumer has demanded. With the objective to contributewith the studies of welfare of the broiler breeder based in the behaviors, this research evaluatesthe dependence of the behaviors of broiler breeders and environment variables, using for this thecoefficient of linear correlation of Pearson. The work was developed with data collected in controlledenvironment, using three breed of broiler breeders. The birds had been submitted the three controlledconditions of temperature and with the measuring of the concentration of the gas ammonia. Positiveand negative linear correlations between the behaviors and environments variables had beenobserved, being able to contribute for future studies of statistical models of welfare estimate